Concepts in abstract algebra - Lanski, Charles (Thomson, 2005)
The style and structure of Concepts in abstract algebra are interded to help students learn the core concepts and associated techniques in algebra deeple anf well. In addition, the text will help students learn the art of constructing mathematical arguments. It helps students to learn the definitions and results and gives mearning to them via extensive discussion, example, development in nontrivial contexts, repetition, and se in exercises...